Crustal investigations from explosion data along Kaveli-Udipi Section of Peninsular India - CHAUDHURY, H. M.; SRIVASTAVA, H. N.; KAMBLE, V. P.; DUBE, R. K.; VERMA, R. K.; VERMA, G. S. (MAUSAM, 1984)
Explosion data collected during 1972- 75 from the deep seismic sounding (DSS) field experiments carried along the Kaveli - Udipi profile under the lndo-Soviet collaboration project has been analysed and interpreted. The velocity of the phases Pg, P* , Pn have been found to be 5.97,± 0.00, 6.81 ± 0.04 and 8.18 ± 0.15 km/sec and for Sg, S*, Sn to be 3.60 ± 0.00, 4.01 ± 0.02, 4.75 ± 0.03 km/sec respectively. A two layered crustal model has been interpreted from the refraction studies for the region. The average thickness of the granitic layer has been found to be 22.4 km and that of basaltic layer to be 16.2 km giving 38.6 km as the depth of Moho. The results obtained from reflection studies broadly confirm the above results. Relationship of the variation of P phase amplitude with charge size and epicentral distance has been derived for three sectors corresponding to the three field seasons along the profile.